2009
DOI: 10.1186/1476-072x-8-65
|View full text |Cite
|
Sign up to set email alerts
|

A trend analysis and sub-regional distribution in number of people living with HIV and dying with TB in Africa, 1991 to 2006

Abstract: BackgroundThe tuberculosis (TB) bacillus and the Human Immunodeficiency Virus (HIV) have formed a powerful alliance and are together responsible for more than five million deaths per year. TB is leading to increased mortality rates among people living with HIV/acquired immunodeficiency syndrome (AIDS). The aim of this study was to investigate the geographical and temporal distribution of TB-HIV deaths in Africa in order to identify possible high-risk areas.MethodsTime trends in the 16-year study period from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
10
0
6
Order By: Relevance
“…22 A tuberculose é comum no curso da infecção pelo HIV. 23 Ela é responsável pelo aumento da mortalidade em soropositivos, sendo um dos motivos pelos quais a sorologia de cada paciente diagnosticado com TB é recomendada. O registro de sorologias não foi verificado em grande parcela dos dados averiguados, contra a lógica necessária à estruturação de um plano de Saúde Pública que previna e reduza as mortes por TB-HIV.…”
Section: Discussionunclassified
“…22 A tuberculose é comum no curso da infecção pelo HIV. 23 Ela é responsável pelo aumento da mortalidade em soropositivos, sendo um dos motivos pelos quais a sorologia de cada paciente diagnosticado com TB é recomendada. O registro de sorologias não foi verificado em grande parcela dos dados averiguados, contra a lógica necessária à estruturação de um plano de Saúde Pública que previna e reduza as mortes por TB-HIV.…”
Section: Discussionunclassified
“… 2-8 However, the greatest challenge for sub-Saharan Africa has been that most HIV-infected patients present late for ARVS thereby increasing the risk of death in spite of the increasing availability of effective treatment. 2 , 6 , 7 The recent changes in WHO treatment guidelines, 9 , 10 recommending treatment initiation at 350-500 cells/µL, were meant to address this challenge in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have attributed the main causes of high mortality in African HIV patients starting HAART were low CD4 cell counts and co-morbidities especially tuberculosis at HAART initiation. 2 A study that investigated the geographical and temporal distribution of TB-HIV deaths in Africa, in the period from 1991 to 2006, 6 showed that Eastern, Southern, Western, and Middle Africa experienced an upward trend in the number of reported TB-HIV deaths. Eastern Africa was ranked first in absolute upward trend in number of reported TB-HIV deaths, followed by Southern and Western Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the spatial analysis of certain information, it is possible to evaluate the risks of disease, trends in outbreaks over time and space, and hotspots of infection. In addition, these methods may relate to the design, planning, and distribution of international health resources for treatment, control and prevention facilities and may help mitigate the impact of interference [20][21][22][23]. This study aimed to investigate the dynamics of the trend to predict the spread of diseases with the help of GIS software and spatial patterns of RT-PCR positive SARS-CoV-2 infected people at the provincial level in Nepal from 23rd January to 13th July, 2020.…”
Section: Introductionmentioning
confidence: 99%